“...waterlogged somewhere in mid-Atlantic.” Why American Readers Need Intralingual Translation but don’t often Get it - Denton, John (TTR, 2007)
AbstractThe quotation in the title is a comment on presumed American reception difficulties of British author Sue Townsend’s bestseller The Secret Diary of Adrian Mole Aged 13 3/4 (1982). A number of American reviews of the book and a questionnaire I used with American readers amply demonstrated a (partial) breakdown in transatlantic communication. Does this mean that American readers of British texts where informal register and cultural embeddedness predominate need some form of intralingual translation? As ‘speakers of the same language’ (albeit a pluricentric one) they do not often get it, in consideration of the widely held belief in a common language and culture. Thus, when shared British text producer-receptor pre-established knowledge schemata can no longer be consistently activated, Americans may well be at a disadvantage as compared with readers of interlingual translations.